OmpL1 Is an Extracellular Matrix- and Plasminogen-Interacting Protein of Leptospira spp. - Fernandes, Luis G. V. (American Society for Microbiology, 2012)
Leptospirosis is a zoonosis with multisystem involvement caused by pathogenic strains of the genus Leptospira. OmpL1 is an outer membrane protein of Leptospira spp. that is expressed during infection. In this work, we investigated novel features of this protein. We describe that OmpL1 is a novel leptospiral extracellular matrix (ECM)-binding protein and a plasminogen (PLG) receptor. The recombinant protein was expressed in Escherichia coli BL21(DE3) Star/pLysS as inclusion bodies, refolded, and purified by metal-chelating chromatography. The protein presented a typical β-strand secondary structure, as evaluated by circular dichroism spectroscopy. The recombinant protein reacted with antibodies in serum samples from convalescent leptospirosis patients with a high specificity compared to serum samples from individuals with unrelated diseases. These data strengthen the usefulness of OmpL1 as a diagnostic marker of leptospirosis. The characterization of the immunogenicity of recombinant OmpL1 in inoculated BALB/c mice showed that the protein has the capacity to elicit humoral and cellular immune responses, as denoted by high antibody titers and the proliferation of lymphocytes. We demonstrate that OmpL1 has the ability to mediate attachment to laminin and plasma fibronectin, with K(D) (equilibrium dissociation constant) values of 2,099.93 ± 871.03 nM and 1,239.23 ± 506.85 nM, respectively. OmpL1 is also a PLG receptor, with a K(D) of 368.63 ± 121.23 nM, capable of generating enzymatically active plasmin. This is the first report that shows and characterizes OmpL1 as an ECM-interacting and a PLG-binding protein of Leptospira spp. that may play a role in bacterial pathogenesis when expressed during infection.